Anomalous Arrhenius and Berthelot behavior of temperature dependent photoluminescence of Mn-doped ZnS nanostructures. Issue 7 (May 2020) - Aziz, Liaquat; Sabih, Nashmia; Mehmood, Shahid; Ali, Awais; Hassan, Muhammad Umair; Bhatti, Arshad Saleem
Abstract: We studied charge carrier relaxation in ZnS:Mn nanostructures synthesized by vapor-liquid-solid (VLS) technique for increasing thickness ( t c  = 0.5, 1 and 3 nm) of thermal deposited Mn catalyst. The dominant phase of the synthesized ZnS:Mn nanostructures was hexagonal Wurtzite, and no trace of secondary phase was observed. The longitudinal optical (LO) and transverse optical (TO) Raman modes in these structures were found at 269 and 348 cm −1, respectively, which were typical of Wurtzite ZnS. Temperature-dependent photoluminescence (PL) spectroscopy showed violet band-to-band transition (~380 nm) along with defect related blue and green bands (~420 and 510 nm), while Mn:d→d band peak was observed at ~ 570 nm. In addition, red band (~670 nm) showed strong appearance at low temperature (10 K) and disappeared at high temperatures was attributed to the formation of possible MnS clusters present in the ZnS:Mn nanostructures. The PL integrated intensities of various bands demonstrated mixed anomalous Berthelot and Arrhenius behavior with increase in temperature. All the emission bands obtained from ZnS:Mn ( t c  = 3 nm) nanostructures showed a Berthelot-type behavior, where the carrier escape (activation) energies were found to be 29 ± 2 (2.3 ± 0.3), 21 ± 1 (2.6 ± 0.5), 11 ± 1 (1.8 ± 0.4) meV and 51 ± 3 meV (1.5 ± 0.1 meV) for the 390 nm, 470 nm, 520 nm and 670 nm bands, respectively. The green and red band of ZnS:Mn ( t c  = 0.5 nm) nanostructures showed a normal Arrhenius behavior whereas, the violet band exhibited the abnormal Berthelot behavior. Increasing Mn thickness also exhibited large modulation of color perception, which is critical to realize single active-layer white light-emitting diodes.